International Knowledge Spillovers and Economic Growth: New Evidence from High-Tech Imports and R&D Cooperation - Mustafa Gömleksiz (İstanbul İktisat Dergisi)
The diffusion of knowledge is an essential triggering factor in the phase of economic growth through externalities mostly based on R&D and innovations embodied in technological products or services. As a form of transmission, knowledge spillovers arising from an external source can emerge through various channels. This study investigates the effect of knowledge spillovers via high-tech imports and international R&D cooperation on longrun economic growth, in a panel of selected emerging and developing economies for the 1995-2019 period. Based on the results of second-generation econometric methods that take into account cross-section dependence and parameter heterogeneity, it is concluded that knowledge spillovers via high-tech imports are a prominent determinant of economic growth. The results also confirm the growth-enhancing effect of domestic knowledge stock as a measure of knowledge absorption capacity. However, it is deduced that knowledge spillovers via R&D cooperation have a weak and somewhat insignificant positive impact on economic growth, when ignoring the complementary relationship between incoming knowledge and the absorptive capacity of countries. Accordingly, the results indicate the essential role of increasing absorptive capacity in gains from R&D spillovers. Lastly, human capital seems to be decisive in the growth process.